2022
DOI: 10.1038/s41598-022-20049-2
|View full text |Cite
|
Sign up to set email alerts
|

Changes in preterm birth and birthweight during the SARS-CoV-2 pandemic: a nationwide study in South Korea

Abstract: Birthweight is a strong determinant of a neonate’s health. The SARS-CoV-2 pandemic’s impact on birthweight has not been investigated in-depth, with inconsistent conclusions from initial studies. To assess changes in preterm birth and inappropriate birthweight between the SARS-CoV-2 pandemic and pre-pandemic periods. A nationwide birth micro-data consisted with exhaustive census of all births in 2011–2020 in South Korea was accessed to examine whether the mean birthweight and rates of under/overweight births ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…9,10, Eleven were included in time-adjusted analysis (Appendix E). 10,35,59,75,125,150,[152][153][154][155][156] The study selection process is summarized in a PRISMA owchart (Figure 1). Most papers included in this review had low risk of bias, although two studies exploring maternal mental health scored poorly on the bias assessment (Appendix D & E).…”
Section: Resultsmentioning
confidence: 99%
“…9,10, Eleven were included in time-adjusted analysis (Appendix E). 10,35,59,75,125,150,[152][153][154][155][156] The study selection process is summarized in a PRISMA owchart (Figure 1). Most papers included in this review had low risk of bias, although two studies exploring maternal mental health scored poorly on the bias assessment (Appendix D & E).…”
Section: Resultsmentioning
confidence: 99%
“…The present study was carried out between 2020 and 2023. In both centres, as reflected worldwide, the SARS-CoV-2 pandemic led to a decrease in preterm baby births during the lockdown period [52,53]. In addition, a higher proportion of patients than expected were not considered initially eligible, and another significant proportion of infants were excluded after randomization.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is known that the pandemic affected the trend in birth outcomes in other countries. Although the results varied from one country to the next, it was suggested that trends in birth outcomes, such as the rates of preterm birth, LBW, and stillbirth changed during the pandemic in certain countries [ 12 15 ]. In Japan, there are some studies that investigated trends in birth outcomes, and one study showed that the number of total births significantly decreased in Japan after the pandemic [ 16 ].…”
Section: Introductionmentioning
confidence: 99%